model promosi ayo berolahraga di komplek olahraga wiradadaha kota tasikmalaya - Marwan, Iis; Rahmat, Agus Arief; Rohyana, Aang (Jurnal Pengabdian Siliwangi, 2020)
Sports are all systematic activities to encourage, foster, and develop physical, spiritual, and social potential. then sports are divided into 5 (five) categories: 1) educational sports; 2) recreational sports; 3) sports achievements; 4) amateur sports; 5) professional sports; and 6) sports with disabilities, (Law No. 3 of 2005, article 1). Wiradadaha sports complex in the City of Tasikmalaya, as one of the areas for sports activities; football field; volleyball, basketball, tennis court; rock climbing, softball, and gymnasium to be used for gymnastics, martial arts, badminton. Land area of more than 15 ha. The government makes arrangements so that users are more comfortable sporting activities. Although sports facilities and infrastructure are quite representative, nevertheless the people who visit tend to decrease, especially outside Saturday and Sunday are lonely visitors so that many sports facilities are not used. The people exercising no longer use the wiradadaha sports complex and tend to move to the Tasikmalaya City square. To overcome these problems, it is necessary to create a promotional model that can stimulate people to come to exercise. The purpose of implementing community service is to create and design promotional models so that people come to exercise at the Wiradadaha sports complex in Tasikmalaya City. Partners are carried out together with the Culture and Sports Tourism Office, KONI, KONI Members Sports Branches, and sports activists in Tasikmalaya City.From the results of focus group discussions attended by sports stakeholders it was agreed that the Tasikmalaya City government needed to provide megatront television, banners, baligo in the sports complex, the sports branch needed to be proactive in promoting its activities so that the community was more interested in joining.